Systematic review: The potency of Zataria multiflora Boiss in treatment of vaginal infections - Mohaddese Mahboubi Mahboubi (Asociación Colombiana de Infectología, 2018)
Vaginitis as female infectious disease is accompanied with some clinical symptoms such as vaginal abnormal discharges, itching, burning and many other unpleasant signs in patients. The responsable microorganisms in vaginitis are belonged to different kind of microorganisms including bacteria (Gardenella vaginitis), yeast (Candida albicans) and protozoa (Trichomonas vaginalis). The current treatments of these infections are chemical oral and vaginal drugs with many adverse effects for patients. Furthermore, appearance of resistant microorganisms to these drugs has intensified the treatment's problem. The aim of this review article was to evaluate the potency of "Zataria multiflora" essential oil in treatment of women's vaginitis. For preparing this manuscript, the information was extracted from different electronic and published resources. Investigation in different resources showed there were 6 clinical trials that evaluate it as suitable treatment for vaginitis. 5 clinical studies have been focused on 0.1% Z. multiflora essential oils in treatment of bacterial vaginosis (n=1), candidiasis (n=1) and trichomoniasis (n=1). Two clinical studies were related to treatments of bacterial vaginosis, trichomoniasis and mixed infection. There is one clinical study for treatment of candidiasis by 1% Z. multiflora methanol extract. Z. multiflora was formulated in cream form and applied for 5-7 continuous days. The results of clinical trials showed that Z. multiflora essential oil (0.1%) can be used as safe and efficient alternative treatment for treatment of bacterial vaginosis, candidiasis and to a lesser extent for trichomoniasis.